2001
DOI: 10.1182/blood.v98.10.3097
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of bactericidal activity in chronic granulomatous disease cells by glucose-oxidase–containing liposomes

Abstract: Chronic granulomatous disease (CGD) is an inherited primary immunodeficiency characterized by phagocytes devoid of a functioning nicotinamide adenine dinucleotide phosphate (NADPH) oxidase. The failure of CGD phagocytes to produce reactive oxygen species (ROS) results in a marked increase in the susceptibility of affected patients to life-threatening bacterial and fungal infections. This study investigated whether loading of CGD phagocytes with glucose oxidase (GO)-containing liposomes (GOLs) could restore cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…In contrast to other studies [38,[45][46][47][48], our approach uses the A. niger-derived GOX in an unbound form and at well-defined concentrations, allowing to increase and titer steady-state H 2 O 2 concentrations to levels comparable to those sustained by activated neutrophils and Kupffer cells in vivo [19,20]. GOX is rapidly phagocytosed and, after a transient passage via the spleen, eventually and exclusively targeted to the liver sinus with a maximum activity after 16 h. In the liver it is primarily found in Kupffer cells as shown by immunofluorescence.…”
Section: Discussioncontrasting
confidence: 68%
“…In contrast to other studies [38,[45][46][47][48], our approach uses the A. niger-derived GOX in an unbound form and at well-defined concentrations, allowing to increase and titer steady-state H 2 O 2 concentrations to levels comparable to those sustained by activated neutrophils and Kupffer cells in vivo [19,20]. GOX is rapidly phagocytosed and, after a transient passage via the spleen, eventually and exclusively targeted to the liver sinus with a maximum activity after 16 h. In the liver it is primarily found in Kupffer cells as shown by immunofluorescence.…”
Section: Discussioncontrasting
confidence: 68%
“…Neutrophils were isolated from the density gradient centrifugation pellet by hypotonic lysis of the remaining erythrocytes using 0.156 M ammonium chloride (18). Neutrophils were washed twice with PBS (Biochrom) and counted with an ultra plane Neubauer hemocytometer.…”
Section: Methodsmentioning
confidence: 99%
“…The central role of the NOX2 system in host defense is demonstrated by the inherited condition chronic granulomatous disease (CGD) in which phagocytes genetically defective in NOX2 or one of its interacting regulatory subunits fail to kill ingested microorganisms, despite normal phagocytosis, resulting in frequent and chronic infections in affected individuals. Definitive evidence for the microbicidal role of ROS was provided by experiments which showed that exogenous H 2 O 2 could restore the ability of defective neutrophils from CGD neutrophils to kill microorganisms (87). Neutrophils from mice in which NOX2 or one of its regulating subunits is genetically deleted show identical microbicidal defects (119,223).…”
Section: Professional Phagocytesmentioning
confidence: 99%